ORGANIZATION OF WORK ON SPEECH DEVELOPMENT OF PRESCHOOL CHILDREN IN MONTESSORI EDUCATION - Bakirova Umida Bakhtiyor kizi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article deals with the organization of work on the development of speech of preschool children in Montessori education. The analysis of approaches to the organization of speech education of preschoolers in classical Montessori pedagogy is presented. A system of work on the development of children's speech in Montessori education is proposed, taking into account modern requirements for the development of the native language by preschool children.